The role of social support and innovation for tempeh business sustainability in Tempeh village - Evie, Benedicta; Jacobus, Yolanda Nadia (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
Tempeh is a well-known source of protein in Indonesia; the ever-increasing price of soybeans makes tempeh artisans feel unsupported by the government. The purpose of the study was to determine the role of social support for women tempeh artisans in developing innovations in the tempeh business. The support received and innovation is expected to help the sustainability of tempeh artisans. This research uses quantitative methods analyzed using SEM-PLS. The research respondents were a community of women tempeh craftsmen in Ciomas; the research was conducted from July to October 2023. The three hypotheses proposed in this study showed positive and significant results. P Value in all three hypotheses is smaller than 0.05. The results show that social support influences the development of tempeh-processed product innovation. Research shows that social support and innovation encourage the sustainability of tempeh artisans’s businesses in Kampung Tempeh Ciomas. Research also shows that women need information and instrumental support to build sustainable businesses. The research concluded that women need training and business assistance to help produce innovations in various processed tempeh products. Women need social support to help realize sustainable businesses. Women need instrumental support through mentoring and training to create product innovations that support business sustainability.